Digital modulation and coding for satellite optical feeder links with pre‐distortion adaptive optics. (11th November 2015) - Dimitrov, Svilen; Barrios, Ricardo; Matuz, Balazs; Liva, Gianluigi; Mata‐Calvo, Ramon; Giggenbach, Dirk
Summary: In this paper, a packet‐level forward error correction coding technique and pre‐distortion adaptive optics technology are applied to a digital transmission scheme for optical feeder links in a geostationary Earth orbit satellite communication system. The architectures of the gateway and the satellite are defined, including the building blocks of the interface between the radio frequency front‐end and the optical front‐end, as well as the digital signal processor. The system is designed to cater for Terabit/s high‐throughput satellite applications. The performance of the digital transmission scheme is evaluated in the forward and return links. The turbulent atmospheric optical channel is modeled for different optical ground station altitudes. It is shown that fade mitigation techniques such as packet‐level forward error correction coding and pre‐distortion adaptive optics in the forward link, as well as large‐aperture optical ground station telescope in the return link, are essential to close the link budget of a Terabit/s satellite communication system. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Packet‐level forward error correction coding and pre‐distortion adaptive optics are applied to digital transmission for optical feeder links in a geostationary Earth orbit satellite communication system. The architectures of the gateway and the satellite are defined, including the building blocks of the interface between the radio frequency front‐end and the optical front‐end, as well as the digital signal processor. The performance is evaluated in the turbulent atmospheric channel. The system is designed to cater for Terabit/s high‐throughput satellite applications.